2022
DOI: 10.3390/biom12070900
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Zinc and Zinc Homeostasis on the Intestinal Mucosal Barrier and Intestinal Diseases

Abstract: Zinc is an essential trace element for living organisms, and zinc homeostasis is essential for the maintenance of the normal physiological functions of cells and organisms. The intestine is the main location for zinc absorption and excretion, while zinc and zinc homeostasis is also of great significance to the structure and function of the intestinal mucosal barrier. Zinc excess or deficiency and zinc homeostatic imbalance are all associated with many intestinal diseases, such as IBD (inflammatory bowel diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 130 publications
0
27
0
Order By: Relevance
“…The in-silico integrative analysis of the lncRNAs and miRNAs (RNA-seq analysis data) shows that the possible target genes of these miRNAs are related to the signaling pathways of transcriptional factors and inflammation pathway mediated by cytokines and chemokines. Zinc, as a signaling molecule, is critical to maintain proliferative cellular capacity that allows self-renewal of intestinal cells to maintain homeostasis of the intestinal epithelium [ 30 ]. The cytokine- and chemokine-mediated inflammation pathway includes key protein/lncRNAs/miRNAs in intercellular communication that help maintain intestinal homeostasis [ 31 ], as well as driving intestinal inflammation in various pathological processes [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The in-silico integrative analysis of the lncRNAs and miRNAs (RNA-seq analysis data) shows that the possible target genes of these miRNAs are related to the signaling pathways of transcriptional factors and inflammation pathway mediated by cytokines and chemokines. Zinc, as a signaling molecule, is critical to maintain proliferative cellular capacity that allows self-renewal of intestinal cells to maintain homeostasis of the intestinal epithelium [ 30 ]. The cytokine- and chemokine-mediated inflammation pathway includes key protein/lncRNAs/miRNAs in intercellular communication that help maintain intestinal homeostasis [ 31 ], as well as driving intestinal inflammation in various pathological processes [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, zinc homeostatic imbalance is associated with many intestinal diseases. 9 For decades, the nanomedicine field was found to improve treatment outcomes for millions of patients. 10 Recently, zinc nanoparticles (Zn-NPs) are used widely in biomedicine, especially as anticancer and antibacterial, due to their protective and beneficial effects.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that impaired physical activity may be correlated with serum zinc levels [ 10 , 11 , 12 ]. Zinc deficiency in the geriatric population may be caused by age-related physiological changes, including reduced saliva secretion, decreased smell and taste perception [ 13 ], degenerative changes in the intestinal microvilli [ 14 ] and deterioration of cognitive or muscle function [ 15 ]. These physiological alterations contribute to inadequate zinc intake and zinc malabsorption, leading to zinc deficiency.…”
Section: Introductionmentioning
confidence: 99%